Flies succession occuring on covered and uncovered rabbit carcasses in Puncak Alam, Selangor / Masitah Muar - Muar, Masitah (2015)
Forensic entomology is the study of insects and arthropods in investigations of criminal cases. Flies are the major type of insects that contribute to medico-criminal investigations. Their succession on cadavers are often used to estimate the Post Mortem Interval (PMI). However, in Malaysia, knowledge on the flies succession of particular conditions of human cadaver especially the one which disposed in zipped suitcases is minimal. The aim of this study was to investigate the succession of flies and their species diversity over the decomposition process of rabbit carcasses concealed in a zipped bag. A triplicate study was done to six male rabbits (Oryctologus cuniculus) under two sets of carcasses conditions, which are concealed in a bag (covered) and normal (uncovered). Observation and data collection were done for 14 days at the study site of UiTM Puncak Alam, Selangor (3°12'23.9"N, 101°27'OO.6"E). There were four families of diptera recorded in this study, which are Calliphoridae, Muscidae, Sarcophagidae and Phoridae. Flies succession in covered carcasses is higher compared to uncovered carcasses, with Chrysomya megacephala, Chrysomya rujifacies and Ophyra sp. being the most abundant species in both conditions of the carcasses. All species arriving on both conditions .are the same. The decomposition rate of covered carcasses is slower than in uncovered carcasses. Data collected in this study can hopefully serve as the basis for future studies on forensic cases involving body disposal in suitcase in Malaysia.